Perception Is Reality: How CEOs’ Observed Personality Influences Market Perceptions of Firm Risk and Shareholder Returns - Harrison, Joseph S.; Thurgood, Gary R.; Boivie, Steven; Pfarrer, Michael D. (Academy of Management Journal, 2020)
We develop theory to explain how CEOs’ observable personality traits influence market perceptions of firm risk and shareholder returns. Using a linguistic tool to measure nearly 3,000 CEOs’ personality traits, we find that CEOs’ observed levels of conscientiousness, neuroticism, and extraversion have important consequences for the perceived riskiness of the firm, as reflected in stock volatility. We also find that these traits alter the relationship between stock risk and returns. Whereas financial economic theory generally posits a positive relationship between risk and returns, on average, we find that this relationship may be either positive or negative for a specific firm depending upon the observed personality of its CEO. Our theory and findings extend upper echelons research by showing that CEOs’ personality traits not only affect market perceptions of the firm but also how those perceptions translate into value creation.